Implementasi Pendidikan Multikultural Dalam Praktik Pendidikan Islam di Indonesia - Maulana, Abiyan; Istikomah; Mubin, Nurul (Cahaya Ilmu Bangsa Institute, 2024)
Indonesia is a large country with all the cultures and customs inherent in it, the diverse cultures cannot be denied that it will give birth to various views that Indonesia is a country with diverse ethnicities, races, cultures and religions. The science that studies this diversity is often referred to as the term Multicultural education. Therefore, the main problem that will be discussed is how to implement multicultural education in Islamic education practices. This article uses library research where the data sources are obtained through library data, including from journals and the internet. With data analysis using a descriptive analysis approach. The data presented in the form of qualitative literature. In its implementation, multicultural education in Islamic religious education goes through several stages, namely; 1) integration of multicultural values ​​in the curriculum, 2) application of collaborative learning, 3) Multicultural extracurricular activities 4) teacher training on Multiculturalism. Multicultural education is the right approach to answer the challenges of diversity in Indonesian society which is multiethnic, multilingual, and multireligious. In the practice of Islamic education, multicultural education plays an important role in instilling values ​​of tolerance, respecting differences, and recognizing the importance of diversity as part of the will of Allah SWT.